A fluorimetric method for red blood cell sorbitol dehydrogenase activity. Issue 6 (June 1983) - Vaca, G; Zúñiga, P; Medina, C; Alonso, R; González-Quiroga, G; Ortíz-De-Luna, R I; Cantú, J M
Abstract : A new fluorimetric method for the quantification of red blood cell (RBC) sorbitol dehydrogenase is described. It is based on the oxidation of sorbitol to fructose, in presence of NAD+, catalysed by the RBC-sorbitol dehydrogenase. The quantity of NADH formed is then measured in a filter fluorimeter. Comparison with an indirect spectrophotometric assay yielded good correlation; however, the present method offers several advantages: it is more rapid, simple and inexpensive. It should be useful to screen for sorbitol dehydrogenase deficiency in large numbers of individuals, particularly patients with diabetes or cataracts.